De Novo Tumors of Teratoma: Ganglioneuroma Arising From a Mature Cystic Teratoma of the Ovary. (May 2018) - Coy, Shannon; Meserve, Emily; Berkowitz, Ross; Hirsch, Michelle S.
Abstract : Mature teratomas are the most common ovarian neoplasms, accounting for 40% to 50% of ovarian tumors, and are histologically defined by the presence of multiple lineages of mature differentiated cells derived from one or more of the 3 embryonic germ layers; ectoderm, mesoderm, and endoderm. Neuroectodermal and neural crest differentiation can be observed in mature teratomas, but it is uncommon to find secondary tumors that arise from the neural crest lineage. Herein we report the uncommon finding of a ganglioneuroma arising in a mature cystic teratoma in a 26-yr-old woman.